2021
DOI: 10.32840/2522-4263/2021-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Current State and Trends of Development of the Agricultural Complex of Ukraine

Anton Chub

Abstract: The purpose of the article is to analyze the current state of the agro-industrial complex of Ukraine, identify development trends and assess the crop and livestock industry, study the commodity structure of foreign trade, develop a mechanism for the development of the agro-industrial complex of Ukraine in the future. The agro-industrial complex of Ukraine is an important industry, which, in turn, is a set of several interrelated industries aimed at processing raw materials and production of agricultural produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As such, A. Chub (2021) research demonstrated that animal husbandry constitutes an integral and crucial component of Ukraine's agro-industrial complex. The importance of this branch of the economy is determined by the need to provide food products of animal origin in the population's diet.…”
Section: Introductionmentioning
confidence: 99%
“…As such, A. Chub (2021) research demonstrated that animal husbandry constitutes an integral and crucial component of Ukraine's agro-industrial complex. The importance of this branch of the economy is determined by the need to provide food products of animal origin in the population's diet.…”
Section: Introductionmentioning
confidence: 99%
“…In the conditions of a favourable temperate climate, the large size of cultivated areas, a significant number of the employed population, and high soil fertility create a unique agricultural potential of the agrarian sector. Thus, in recent decades, the volume of production of grain and leguminous crops, as well as sunflower, has been rapidly growing (Chub, 2022). Despite the large production capacities of agricultural enterprises, there is a gap between the available and the maximum possible productivity of agricultural production (Lupenko & Andros, 2020).…”
Section: Introductionmentioning
confidence: 99%